Optimising in vitro Somatic Embryogenesis in Polyembryonic Mango (Mangifera indica L.) Varieties - Bindu C P (Department of Horticulture, College of Agriculture, 1995)
Studies were conducted to optimise the in vitro propagation techniques via somatic embryogenesis in polyembryonic mango varieties (Vellari, Kalluvarikka, Thalimanga, Kilichundan, Pulichi and Varikka) of Kerala, during 1993-1994 at the Department of Horticulture, College of Agriculture, Vellayani. Culture media and conditions could be standardised for the first two stages of somatic embryogenesis, namely